Redesign of Takada radio using Boothroyd Dewhurst DFA method - Mohamed Kader Maidin, Y. Shahari (2009)
The present paper discusses the Boothroyd Dewhurst DFA method that been used to evaluate a radio named Takada radio based on assembly efficiency. A survey conducted by distributing questionnaire about Takada radio to the university students and manufacturing company workers. Original design of Takada radio is analyzed and redesign of Takada radio is created based on improved assembly efficiency. Main thing evaluated in this project on Takada radio is the total assembly time and cost, and percentage of design efficiency. ALGOR software analysis is used to evaluate the reliability of the integral fasteners that have been designed in the redesign of Takada radio. The integral fasteners are analyzed on whether it will break or failure under range of forces acted on the integral fasteners. The redesign of Takada radio with the higher percentage value of design efficiency is selected as the best design in term of its assembly efficiency.